Transport and structural properties of Cu0.25Bi2(TexSe1−x)3 (x = 0.01) under high pressure. (10th April 2017) - Ohmura, Ayako; Matsuzawa, Masako; Ishikawa, Fumihiro; Suzuki, Yusuke; Komatsu, Masashi; Osuga, Shumpei; Nakano, Satoshi; Nakayama, Atsuko; Yamada, Yuh; Kashiwagi, Takanari; Kadowaki, Kazuo
Abstract: Cu0.25 Bi2 (Te x Se1− x )3 is a material in which tellurium atoms (Te) partially occupy selenium (Se) sites in a crystal structure of the superconductor Cu0.25 Bi2 Se3 . This study focuses on the composition of x = 0.01, Cu0.25 Bi2 (Te0.01 Se0.99 )3, and we performed electrical resistivity measurement and X-ray diffraction under high pressures. Cu0.25 Bi2 (Te0.01 Se0.99 )3 shows slight diamagnetism and a drop in resistivity at ambient pressure; this suggests possible superconductivity at the transition temperature of T c = 3.2 K, which is suppressed at P = 1 GPa. On further compression, a slight drop in resistivity is observed at temperatures of 4.3–5.4 K above 10 GPa. This drop is suppressed under magnetic fields, suggesting the occurrence of superconducting transition. The pressure-induced structural phase transition from a trigonal phase to a sevenfold monoclinic C 2/ m phase occurs at 10.9 GPa. These results suggest that the superconducting transition above 10 GPa occurs in the high-pressure C 2/ m phase.